A study on precautionary steps in purchasing goods online / Yuhanza Othman... [at al.] - Othman, Yuhanza; Ahmad Mustafa, Mimi Sofiah; Mohamad Roseli, Nur Hazwani; Hasan, Zuhairah; Hasan, Rahayu (UiTM Cawangan Johor, 2019)
Despite significant development on online transactions in Malaysia, there are also risks and challenges in their applications. Previous researchers contended that, the Malaysian statutes do not sufficiently protect the online shoppers. Although the law requires that the goods purchased must correspond with the descriptions, the online shoppers still need to take certain precautionary steps to avoid from being cheated. The objectives of this research are to explore the precautionary steps taken by online shoppers before they purchased goods online and to analyze their experiences that may influence purchasing decision. This doctrinal research adopted a qualitative method where 30 respondents were interviewed. The result shows various actions taken by them before purchasing online and most of them rely on their experience before they proceed with second purchases. Thus, this research will enlighten and suggest the precautionary steps for online consumers to adhere to in order to avoid unnecessary risks in purchasing online.